The Write Thing : Kwame Alexander Engages Students in Writing Workshop (and You Can Too!). - Alexander, Kwame (Professional Resources Ser., 2018)
Newbery Medal-winning author Kwame Alexander shows how to shake up the traditional writing workshop to make writing fun again. Using his techniques and strategies, you'll invigorate the writing workshop and motivate even the most reluctant writers.